METODE PEMBERIAN BALIKAN UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA SISWA - Tuty Setijani (Universitas Negeri Surabaya, 2022)
The main task of a teacher is to be responsible for helping students in learning. In the teaching and learning process, it is the teacher who delivers lessons, solves problems that occur in class, makes evaluations of student learning, both before, during and after the lesson. The problems to be studied in this action research are: (a) Does learning by giving feedback affect student learning outcomes? (b) How is the effect of learning by giving feedback on students' learning motivation? Meanwhile, the objectives of this research are: (a) To reveal the effect of learning by giving feedback on mathematics learning outcomes. (b) To reveal learning by giving feedback on the motivation to learn Mathematics. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the fifth grade students of SDN Dukuh Menanggal I/424 Surabaya. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. The objectives of this action research are: a) To reveal the effect of learning by giving feedback on learning achievement in Mathematics, (b) To reveal learning by giving feedback on motivation to learn science. From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle III, namely, cycle I (69.44%), cycle II (80.56%), cycle III ((88.89%). is learning by giving feedback can have a positive effect on the learning motivation of SDN Dukuh Menanggal I/424 Surabaya students, and this learning model can be used as an alternative to learning mathematics.